Anatomia radiográfica da região proximal do fêmur: correlação com a ocorrência de fraturas - Pires, Robinson Esteves Santos (2012)
OBJECTIVE: To evaluate the correlation between radiographic parameters of the proximal femur anatomy and fractures. METHODS: Three hundred and five digital x-rays of the pelvis were analyzed in the anteroposterior view. Of these x-rays, twenty-seven showed femoral neck or transtrochanteric fractures. The anatomical parameters analyzed were: femoral neck width (FNW), femoral neck length (FNL), femoral axis length (FAL), cervicodiaphyseal angle (CDA), acetabular tear-drop distance (ATD) and great trochanter-pubic symphysis distance (GTPSD). The analysis was performed by comparing the results of the x-rays with and without proximal femoral fracture, to establish a correlation between them. RESULTS: No differences were found between the anatomical parameters of the groups with and without proximal femoral fracture. CONCLUSION: There was no association between anatomical changes in the proximal femur and greater susceptibility to fractures. Level of evidence IV, Cross-sectional Study.